Vibration signatures of a rotor-coupling-bearing system under angular misalignment. (March 2019) - Tuckmantel, Felipe Wenzel da Silva; Cavalca, Katia Lucchesi
Highlights: Numerical analysis of angular misalignment between shafts. Modelling of flexible disc coupling through restoring forces and moments. Analysis of machine operating state and fault condition signature. Comparison between flexible coupling modelling approaches. Comparison of test rig measurements and proposed theoretical approach. Abstract: Forces and moments arise in flexible couplings while accommodating misalignments. These efforts are exerted on the coupled shafts, influencing the rotor dynamics and giving rise to vibration patterns, which are of interest for investigations focusing on malfunction signatures and, consequently, on fault identification and diagnosis. This work proposes the comparison between two approaches for modeling the forces and moments generated by a metallic disc coupling under angular misalignment. The first is a well-established model based on the linear bending flexure of the disc packs, and assuming the misalignment efforts are the sum of the first four harmonic components. In the second approach, a structural analysis of the coupling is conducted through finite element method, where the cyclic nature of coupling efforts is captured by the application of consecutive shaft spin angles. Steady state responses are simulated and then both orbit shapes and displacements spectrum are analyzed in order to highlight harmonic components rising due to misalignment. Finally, test rig measurements are compared to predicted results by the theoretical approach presented in this work.